Planned group counseling : an alternative group method for reluctant chemically dependent and psychiatric patients - Biancoviso, Anthony N. (Springer Pub., 2004)
This book presents a detailed description of a new group method called Planned Group Counseling (PGC). This method was created to cope with the very reluctant behaviors found in chemically dependent and psychiatric patients: lateness, irregular attendance, premature termination, and non-compliance with therapeutic directives. The book provides the readers with a step-by-step guide for implementing PGC, including plans and psychological exercises that are designed to further develop intra-and interpersonal skills. Detailed descriptions of interventions are also included to help the group leader.